International Encyclopedia of Education 2010
DOI: 10.1016/b978-0-08-044894-7.00493-0
|View full text |Cite
|
Sign up to set email alerts
|

Computer-Supported Collaborative Learning: Basic Concepts, Multiple Perspectives, and Emerging Trends

Abstract: Abstract:Computer-Supported Collaborative Learning (CSCL) is the field concerned with how Information and Communication Technology (ICT) might support learning in groups (co-located and distributed). The chapter surveys key studies, common technologies, and significant events in the field. It presents basic concepts, multiple perspectives, and emerging trends in CSCL. A main distinction is drawn between the systemic and the dialogical approach to research. The former is rooted in the cognitive perspective on l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0
5

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(41 citation statements)
references
References 19 publications
2
34
0
5
Order By: Relevance
“…One aspect is represented by the locus of learning, which can be at the individual, the group, or the community level, and expressed in analytic terms by the unit of analysis. This study follows conceptualization by Valsiner & van der Veer (2000), Ludvigsen and Mørch (2010) or Säljö (2004) acknowledging that meaning making and knowledge are constructed in a less-well-charted middle ground of the interaction, involving individual and collective input. Social interaction at the group level, expressed in language and actions, allows us to pin down the important aspects of the knowledge construction effort.…”
Section: An Integrative Analytic Frameworkmentioning
confidence: 99%
“…One aspect is represented by the locus of learning, which can be at the individual, the group, or the community level, and expressed in analytic terms by the unit of analysis. This study follows conceptualization by Valsiner & van der Veer (2000), Ludvigsen and Mørch (2010) or Säljö (2004) acknowledging that meaning making and knowledge are constructed in a less-well-charted middle ground of the interaction, involving individual and collective input. Social interaction at the group level, expressed in language and actions, allows us to pin down the important aspects of the knowledge construction effort.…”
Section: An Integrative Analytic Frameworkmentioning
confidence: 99%
“…Outra iniciativa que impulsionou a divulgação dos trabalhos sobre a temática foi a criação, em 2006, do International Journal of Computer-Supported Collaborative Learning. 2 As origens da CSCL repousam no desenvolvimento de 3 projetos, todos idealizados com o objetivo comum de orientar a educação à constituição de significado, a partir do emprego das TIC, com a incorporação de novas formas de atividade social na instrução. 1 O Eletronic Networks for Interaction (ENFI), da Universidade de Gallaudet (EUA), buscou auxiliar o desenvolvimento da escrita por alunos surdos ou com pouca audição; o Computer-Supported Intentional Learning Environment (CSILE), da Universidade de Toronto (Canadá), buscou o estímulo à escrita dos alunos; o Fifth Dimension, da Universidade da Califórnia em San Diego (EUA), buscou melhorar a habilidade de escrita e de resolução de problemas dos estudantes.…”
Section: Introductionunclassified
“…3,4 Atividades pautadas na CSCL podem ser aplicadas a todos os níveis da educação formal e na educação informal e têm como vantagens a melhora da qualidade das soluções para problemas propostos pelo professor; o compartilhamento dos resultados de pesquisa entre os membros do grupo; a exposição de várias perspectivas e interpretações; a promoção da argumentação; a construção social do conhecimento e a mudança conceitual do indivíduo; diversos tipos de comunicação (aluno-aluno; aluno-professor; professor-aluno). 2 Partindo desse pressuposto, neste trabalho de caráter exploratório temos como objetivo descrever uma atividade didática pautada em interações colaborativas estabelecidas entre estudantes de graduação em Química em um Ambiente Virtual de Aprendizagem (AVA), denominando eduqui.info, desenvolvido no âmbito do Grupo de Pesquisa em Ensino de Química do IQSC (GPEQSC), com o apoio da Fundação de Amparo à Pesquisa do Estado de São Paulo (FAPESP), no qual os estudantes interagiram por meio da ferramenta Fórum em busca da melhor solução para casos investigativos de forma colaborativa. A análise das interações foi realizada com base no Modelo de Aprendizagem Colaborativa, sucintamente descrito a seguir, com o intuito de investigarmos a efetividade da colaboração por meio do desenvolvimento de habilidades de comunicação.…”
Section: Introductionunclassified
“…It is concerned with how information and communication technologies might support learning in groups (located and distributed) (Ludvigsen & Mørch, 2010;Noroozi, Biemans, Busstra, Mulder, & Chizari, 2011;Noroozi, Busstra, et al, 2012). A large number of studies have demonstrated that, in order to improve students' learning outcomes in CSCL, attention should be paid to the nature of the learning processes.…”
Section: Research On Support Components Of Students' Learningmentioning
confidence: 99%